Hybrid Breeding Skewed the Allelic Frequencies of Molecular Variants Derived from the Restorer of fertility 1 Locus for Cytoplasmic Male Sterility in Sugar Beet (Beta vulgaris L.). Issue 4 (1st July 2014) - Taguchi, Kazunori; Hiyama, Hajime; Yui‐Kurino, Rika; Muramatsu, Aki; Mikami, Tetsuo; Kubo, Tomohiko
ABSTRACT: Hybrid breeding of crops may involve the selection of reproductive traits, such as cytoplasmic male sterility (CMS), whose expression is controlled by cytoplasm and nuclear gene(s). Intense selection of a single cytoplasm and the consequent lack of cytoplasmic divergence is a potential danger, the so‐called genetic vulnerability. However, little is known about the relationship between hybrid breeding and the diversity of nuclear genes that suppress the expression of CMS, termed restorer of fertility ( Rf ). Despite the multi‐allelic nature of Rf at the molecular level, a common Rf variant was previously found to predominate in sugar beet maintainer lines that were selected for a specific genotype for propagating the CMS line. The question was raised as to the frequency of the common Rf variant before the hybrid breeding era. As the origin of Japanese maintainer lines can be genealogically traced back to seven nonhybrid cultivars, we investigated the allelic diversity of Rf in the seven cultivars using molecular markers. Our results indicated that Rf diversity differs among the cultivars but exceeds that of the maintainers in total, and the common variant in the maintainers is infrequent in all of the cultivars. Therefore, maintainer selection has involved selecting a small number of Rf variants in the founder population in Japan.